American psychosis : a historical investigation of how the Republican Party went crazy - Corn, David (New York : Twelve, 2022)
"A fast-paced, rollicking account of how paranoia and conspiracy theories have long been major elements within the GOP and how these forces came to triumph under Donald Trump, AMERICAN PSYCHOSIS offers readers a brisk, can-you-believe-this journey through this netherworld of far-right irrationality and explores its interactions with the GOP. It tells the tale of how the Republican Party has turned into a conspiracy cult, kicking ideology and policy principles to the curb in support of a president who embraced and exploited-and stirred-the most bizarre and craziest extremism of the right. The Trump-incited insurrectionist attack on the Capitol on January 6, 2021, was no aberration. AMERICAN PSYCHOSIS reveals it was a continuation of a long and deep-rooted tradition within the party, the result of a derangement on the right that has been accepted and often nurtured by the GOP. AMERICAN PSYCHOSIS entertains and enlightens even as it horrifies, and will be a crucial part of the roiling conversation under way in the run-up to the first post-Trump election. The story told in AMERICAN PSYCHOSIS covers the last half-century; from McCarthyism to the Birchers to segregationists to the religious right to the militia movement to Rush Limbaugh to the tea party and to Donald Trump, the Republican Party has encouraged and exploited right-wing fear and loathing that has been dangerously fueled by conspiracy theories, and now holds the entire United States political process in its grip"--
Backstory I: The rise and decline of the Grand Old Party -- Backstory II: Fear and loathing in America -- The general and the scoundrel -- No bood Birchers -- In your heart -- Keeping the kooks quiet -- "Bring us together" -- Ratfucking America -- "Make them angry" -- Onward Christian soldiers -- Let's make America great again -- Reaganland -- Morning (and Nazis) in America -- Not kinder or gentler -- Spiritual warfare -- The Clinton chronicles -- A vast right-wing conspiracy -- Fortunate son -- What we deserve -- Going rogue -- Feed the beast -- The fever doesn't break -- "I am your voice" -- Very fine people -- Epilogue: the aftermath
Includes bibliographical references (pages 357-369) and index
Keywords: Republican Party (U.S. : 1854- ); Conspiracy theories -- United States -- Psychological aspects; Conspiracy theories -- Political aspects -- United States; Right-wing extremists -- United States; Conservatism -- United States -- 21st century; United States -- Politics and government